2018
DOI: 10.1093/geront/gny121
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of Social Motivation Questionnaire

Abstract: Background and Objectives Information-seeking (IS) and emotion-regulatory (ER) motivation play meaningful roles in age-related changes in social interaction across adulthood. This study aimed to develop and validate the Social Motivation Questionnaire (SMQ) to assess these two types of motivation. Research Design and Methods Ten items were selected from a pool as the candidate items of SMQ and were administered to 480 German … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 59 publications
(82 reference statements)
0
10
1
Order By: Relevance
“…The enhancement motive seems to be less prevalent among the oldest age group than among other age groups. Building further on Gong et al (2019) and Yamashita et al (2019) , a shift in priorities in which adults prioritize present-oriented motives despite their age, such as pursuing emotional meaning and fulfilment when the future time perspective is limited and circumscribed, may help explain the enhancement motives underlying helping behavior during the pandemic. In their decision to provide help, compared to their older peers younger age groups were plausibly also driven to give meaning to their lives from enhancement motives, such as increasing self-esteem and working toward self-development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The enhancement motive seems to be less prevalent among the oldest age group than among other age groups. Building further on Gong et al (2019) and Yamashita et al (2019) , a shift in priorities in which adults prioritize present-oriented motives despite their age, such as pursuing emotional meaning and fulfilment when the future time perspective is limited and circumscribed, may help explain the enhancement motives underlying helping behavior during the pandemic. In their decision to provide help, compared to their older peers younger age groups were plausibly also driven to give meaning to their lives from enhancement motives, such as increasing self-esteem and working toward self-development.…”
Section: Discussionmentioning
confidence: 99%
“…Building further on Gong et al (2019) and Yamashita et al (2019), a shift in priorities related to future-oriented (social interactions that are valued by one’s social group) or present-oriented motives (being focused on family care) may contribute to understanding the motives for helping behavior. A question is whether this pandemic may have altered motivational factors across age groups.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies; compared to younger individuals, older individuals have been shown to be more selective in shaping their social environment (6), interact more with individuals they feel emotionally close to (7), and maintain their interaction with a core close environment for long periods of time (8). At the same time, compared to younger individuals, older individuals experience better quality social relationships (9) and face fewer problems in their relationships (5).…”
Section: Introductionmentioning
confidence: 92%
“…The importance of these social motivations on the individual can be affected by factors such as gender, personality, society and family structure. One of these factors is the age of the individual (5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation